Chelation activity and protective effect of Caulerpa lentillifera aqueous extract against lead acetate-induced toxicity in Sprague Dawley rats - Dzulsuhaimi Daud,, Ahmad Nazrin Zainal, Muhammad Naqib Nordin, Alene Tawang, Asmida Ismail (Journal of Applied Pharmaceutical Science, 2020)
Lead is a multisystemic toxicant when it accumulates and is hazardous to health. This study was conducted to determine the effect of Caulerpa lentillifera aqueous extract on lead accumulation in the internal organs and liver functions of lead-intoxicated rats. Sprague Dawley rats (n = 24) were divided into four groups (n = 6). Group I was healthy rats treated with saline (2 ml/kg bwt) daily for 28 days. Group II was healthy rats treated with C. lentillifera aqueous extract (500 mg/kg bwt) daily for 28 days. Group III was intoxicated with lead acetate (20 mg/kg bwt) daily for 4 days and then treated with saline (2 ml/kg bwt) for another 24 days. Group IV was intoxicated with lead acetate (20 mg/kg bwt) daily for 4 days and then treated with C. lentillifera aqueous extract (500 mg/kg bwt) for another 24 days. Lead accumulation in the internal organs was measured by the atomic absorption spectrophotometer and the liver function markers were determined using assay kits. Lead intoxication significantly (p < 0.05) increased lead accumulation in the rats’ internal organs and affected their liver functions. C. lentillifera aqueous extract supplementation to lead-intoxicated rats significantly (p < 0.05) decreased lead accumulation in the rats’ internal organs and protected their liver functions. This study concludes that C. lentillifera aqueous extract possesses the capability of a chelating agent and attenuates the effect of lead on lead-intoxicated rats.
Keywords: Caulerpa lentillifera, lead, chelation, liver functions, heavy metals.